Adsorption of non-ionic surfactants on organoclays in drilling fluid investigated by molecular descriptors and Monte Carlo random walk simulations - Kania, Dina; Yunus, Robiah; Omar, Rozita; Abdul Rashid, Suraya; Mohamed Jan, Badrul; Aulia, Akmal (Elsevier, 2021)
Non-ionic surfactants have been used as a rheology control additive in drilling fluids to prevent flocculation of solids, such as organoclays, and maintain mud dispersion. Here, the fundamental phenomena involved in non-ionic surfactant adsorption on organoclays and how it affects the rheology of synthetic-based drilling fluids were elucidated by the analysis of molecular descriptors and Monte Carlo simulations. Using the Random Forests machine learning algorithm software, the non-ionic surfactant adsorption on organoclays was found to be affected mainly by the hydrophobicity and molecular shape of hydrophobic chains of non-ionic surfactants. Molecular descriptor calculations indicated that the hydrophobic interaction and van der Waals forces are dominant factors. Then, the Monte Carlo simulations provided the empirical effect of the non-ionic surfactant hydrophobic chains on their self-assembly to organoclays. Molecules with two chains were found to be easily adsorbed to the surface due to molecular size, while molecules with three and four chains occupy more sites and interact with each other more frequently, forming larger clusters. Consequently, non-ionic surfactants with more hydrophobic chains were predicted to improve rheology of drilling fluids and form stable mud emulsions. This approach is useful in predicting the effects of new additive in drilling fluid formulation.